Insights Into Manganese Solubilizing Bacillus spp. for Improving Plant Growth and Manganese Uptake in Maize - Ijaz, Ayesha; Mumtaz, Muhammad Zahid; Wang, Xiukang; Ahmad, Maqshoof; Saqib, Muhammad; Maqbool, Hira; Zaheer, Ahmad; Wang, Wenqiang; Mustafa, Adnan (Frontiers in Plant Science, 2021)
Manganese (Mn) is an essential micronutrient for plant growth that is involved in the structure of photosynthetic proteins and enzymes. The deficiency of Mn is widespread mainly in dry, calcareous, and sandy soil, which leads to a significant decrease in crop yield. Mn-reducing bacteria promote the solubilization of Mn minerals, thus increasing Mn availability in soil. The present study aimed to assess the Mn solubilizing ability and plant growth-promoting potential of Bacillus spp. strains for maize plants with insoluble Mn compounds. Several Mn-solubilizing bacterial (MSB) strains were isolated from the maize rhizosphere using nutrient agar media amended with 50 mM MnO2. These strains were screened based on qualitative and quantitative solubilization of Mn, phosphorus, potassium, and zinc and production of ammonia. The majority of MSB strains were positive for catalase, protease, amylase, and oxidase activity, while more than 60% of tested strains were positive for lipase activity, and the production of indole-3-acetic acid and siderophores. Forty-five percent of the tested strains also showed solubilization of potassium. All the MSB strains were evaluated for their ability to promote plant growth and Mn uptake in the presence of MnO2 under axenic sand culture conditions. The results revealed that inoculation with MSB strains under sand culture significantly improved the growth of maize seedlings except for strains ASH7, ASH10, and ASH12. Comparatively, strains ASH6, ASH11, ASH19, ASH20, and ASH22 demonstrated a better increase in plant growth, fresh and dry biomass, and Mn uptake in roots and shoots than the other strains tested. All of these strains were identified as Bacillus spp. through 16S rRNA partial gene sequencing. Maize inoculation with these selected identified MSB strains also reported an increase in maize growth and nutrient uptake in maize roots and shoots under soil culture conditions in the presence of native soil Mn. The current study highlighted the importance of MSB strain inoculation which could be a potential bioinoculants to promote plant growth under Mn deficiency.